The Punctuation Signs (Pause) in the Quran and Their Effects in Determining the Meaning of the Quranic Texts: A Description and Semantic Study - Mustapha, Maziah; Zakaria, Abd Wahab (IIUM, 2015)
Early Muslim scholars among linguists and Qur'anic experts gave special attention to the Qur'anic punctuation (pause). It is an important area because of its significance in understanding the meaning of the Glorious Qur'an; for both the reciter and the listener. This is so because it distinguishes between different information, rulings and issues during recitation. Given the fact that Quranic recitation varies from one another, the places to pause while reciting also differ accordingly. It should, therefore, be in conformity with the type of recitation one intends to recite at a time in order to maintain the semantic accuracy of the Qur'an. This research intends to analyse the semantic implications of the Qur'anic pause with reference to the seven recitation methods by the early Islamic scholars. The outcome of the research would assist Qur'anic reciters to be aware of the semantic implication of pauses to avoid misrepresenting the meaning of the Quran during recitation.